Characterisation of the effect of alteration on the PPM platinum ore and evaluation of selected strategies to improve metallurgical performance - Ramonotsi, Mpho (Centre for Bioprocess Engineering Research, 2015)
The aim of this study is in two parts; the first part focuses on mineralogical quantification of the extent of weathering at PPM by profiling the flotation behaviour and host rock density with spatial depth.